SCREENING OF ANTI-COLON CANCER ACTIVITY BY USING HYDROALCOHOLIC EXTRACT OF BORASSUS FABILIFERS HOOT ON SWISS ALBINO MICE - SALMA SULTANA SK; BANUREKHA J; KUMAR M (Asian Journal of Pharmaceutical and Clinical Research, 2025)
<!--StartFragment--> Objectives: This study addresses the escalating global incidence of colon cancer, recognized as the most prevalent cancer type. With approximately 4.6% of men and 4.2% of women diagnosed during their lifetime, the urgency to explore effective treatments becomes paramount, given the annual occurrence of 1.23 million new cases worldwide. The primary objective is to investigate the impact of the hydroalcoholic extract of Borassus flabellifer on altered hematological and biochemical parameters induced by azoxymethane (AOM)/dextran sulfate sodium (DSS), identifying potential hepatoprotective effects. Methods: This research utilized 30 mice, with 24 receiving AOM injections and 6 serving as untreated healthy controls. The AOM-injected mice were further subdivided into groups, and treatment with B. flabellifer extract commenced on the 3rd day and spanned 70 days. DSS cycles were administered, and hematological and biochemical parameters were assessed. At the end of the experiment, mice were sacrificed, and the colorectal region was preserved for analysis. Results: Results elucidate the AOM/DSS-induced alterations, including increased serum levels of alanine transaminase, aspartate transaminase, alkaline phosphatase, white blood cell, platelet count, and total protein, indicative of hepatic damage. Conversely, the hydroalcoholic extract significantly reduced these parameters, aligning with previous studies showcasing the plant’s anti-cancer activity. These findings highlight the pharmacological potential of *B. flabellifer* in mitigating colon cancer symptoms. Conclusion: This research underscores the significance of B. flabellifer in countering the rise of colon cancer. The hydroalcoholic extract exhibits promising results in ameliorating AOM/DSS-induced alterations, providing a foundation for further exploration of its therapeutic potential. The study contributes valuable insights into the pharmacological properties of *B. flabellifer* and sets the stage for potential applications in cancer treatment.